2010
DOI: 10.37236/314
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Characterizations of Dumbbell Graphs

Abstract: A dumbbell graph, denoted by $D_{a,b,c}$, is a bicyclic graph consisting of two vertex-disjoint cycles $C_a$, $C_b$ and a path $P_{c+3}$ ($c \geq -1$) joining them having only its end-vertices in common with the two cycles. In this paper, we study the spectral characterization w.r.t. the adjacency spectrum of $D_{a,b,0}$ (without cycles $C_4$) with $\gcd(a,b)\geq 3$, and we complete the research started in [J.F. Wang et al., A note on the spectral characterization of dumbbell graphs, Linear Algebra Appl. 431 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 13 publications
(24 reference statements)
0
30
0
Order By: Relevance
“…We can obtain DQS graphs with independent edges and isolated vertices from Theorem 3.2. [23,30,45,46]. We can obtain DQS graphs with independent edges and isolated vertices from Theorem 3.3.…”
Section: Resultsmentioning
confidence: 99%
“…We can obtain DQS graphs with independent edges and isolated vertices from Theorem 3.2. [23,30,45,46]. We can obtain DQS graphs with independent edges and isolated vertices from Theorem 3.3.…”
Section: Resultsmentioning
confidence: 99%
“…Graphs consisting of two cycles with just a vertex in common are called ∞graphs in [49]. It is proved that ∞-graphs without triangles are characterized by their Laplacian spectra and that all ∞-graphs, with one exception, are characterized by their signless Laplacian spectra.…”
Section: Spectral Characterizationsmentioning
confidence: 99%
“…In Part II we have added the following 11 references: [1], [3], [24], [25], [26], [27], [34], [36], [48], [52], [54]. In the meantime the following 16 papers [2], [13], [18], [19], [21], [28], [29], [30], [31], [32], [38], [42], [45], [49], [51], [53] have been published or are in the process of publication at this moment. Together with [11], [12] and this paper, there are in this moment about 50 papers on the signless Laplacian spectrum published since 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral determinations have been widely studied for unsigned graphs and recently this kind of study has been taken to signed graph spectra, as well. The spectral determination of (unsigned) ∞-graphs, which is the coalescence between two cycles C r and C s and related graphs, has been already considered in [16]. The spectral determination of signed lollipop graph, which is the coalescence between a cycle and a path, has been studied and it is shown that a signed lollipop graph is determined by the spectrum of its Laplacian matrix (or simply DLS) [5].…”
Section: Introductionmentioning
confidence: 99%